Report and recommendation of the president to the board of directors on a proposed loan and technical assistance grant to the Democratic Socialist Republic of Sri Lanka for the plantation reform project (In Asian Development Bank, Manila, Philippines 78p Oct 1995)
A proposal is presented for a loan and technical assistance from the Asian Development Bank for a plantation reform project in Sri Lanka. The proposed project is designed to assist in the rehabilitation and improvement of the existing tea, rubber and coconut estates by the private sector and to enhance the competitive advantage of Sri Lankas tree crop industry. After a review of the tree crops subsector and the government policies and plans pursued to improve the sectors competitiveness, a detailed description of the project is provided.
Source Year: 1996
Keywords: Crop industry; Rubber; Sri Lanka